CONTENT-BASED IMAGE CLASSIFICATION UNTUK IMAGE RETRIEVAL - I Gusti Rai Agung Sugiartha (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTFile sharing services provide large and free space. The increasing need to save files in the form of images, causing the existence of images with various themes stored on the Internet. Users through image search system services in the Internet world, for example Image Google, Bing Images, and others, are able to get images that are searched based on several parameters from the user. Some systems are built to produce image search accuracy, with several techniques. Content-Based Image Retrieval, Text-Based Image Retrieval, and Cluster Image Retrieval are techniques in the Image Retrieval system. Cluster Image Retrieval has the problem of determining the resulting clustering label. Multidimensional image content makes it difficult to generate color, texture, and shape features used in the system. The lian problem is that the cluster formed is likely not a representation of the expected image. The research carried out, using CNN (Convolutional Neural Network) for image classification based on color features, textures, and shapes to support image retrieval systems. The use of classification can improve performance in grouping image categories.Keywords: Image Retrieval, Classification, CNN.ABSTRAKLayanan file sharing menyediakan ruang besar dan gratis. Meningkatnya kebutuhan untuk menyimpan berkas berupa gambar, menyebabkan keberadaan gambar dengan berbagai tema tersimpan di Internet. Pengguna melalui layanan sistem pencarian gambar di dunia Internet, misalnya Image Google, Bing Images, dan yang lainnya, mampu mendapatkan gambar yang dicari berdasarkan beberapa parameter dari pengguna. Beberapa sistem dibangun untuk menghasilkan akurasi pencarian gambar, dengan beberapa teknik. Content-Based Image Retrieval, Text-Based Image Retrieval, dan Cluster Image Retrieval merupakan teknik dalam sistem Image Retrieval. Cluster Image Retrieval memiliki kendala penentuan label clustering yang dihasilkan. Konten gambar yang multidimensional menyulitkan pembangkitan fitur warna, tekstur, dan bentuk yang dipergunakan dalam sistem tersebut. Permasalahan lian adalah cluster yang terbentuk kemungkinan bukan merupakan representasi dari gambar yang diharapkan. Penelitian yang dilaksanakan, menggunakan CNN (Convolutional Neural Network) untuk klasifikasi gambar berdasarkan fitur warna, tekstur, dan bentuk untuk mendukung sistem image retrieval. Penggunaan klasifikasi bisa meningkatkan kinerja dalam pengelompokkan kategori gambar.Kata kunci: Image Retrieval, Klasifikasi, CNN